Advances and challenges in cell therapy for neuropathic pain based on mesenchymal stem cells - Zhang, Wen-Jun; Pi, Xiong-Wei; Hu, Dong-Xia; Liu, Xiao-Ping; Wu, Ming-Ming (Frontiers in Cell and Developmental Biology, 2025)
Neuropathic pain (NPP) is caused by damage to the somatosensory nervous system. Its prominent symptoms are spontaneous pain, hyperalgesia and abnormal pain. This pain is long-lasting and unbearable, seriously affecting the patient’s quality of life. At present, the clinical treatment effect of painkillers to relieve NPP is still not ideal, nor can it repair damaged nerves and achieve long-term treatment results. In recent years, the application of cell therapy strategies in the field of pain has yielded encouraging results, including preclinical studies and clinical trials. Mesenchymal stem cells (MSCs) are pluripotent progenitor cells derived from mesogenesis. They have the ability to self-renew and differentiate into multiple cell types and have been widely studied and applied in the field of neuroregenerative medicine. MSCs play an important mechanism functional role in promoting injured nerve regeneration and pain relief by regulating multiple processes in target cells, including immunoregulation, anti-inflammatory properties, promoting axon regeneration and re-myelination, promoting angiogenesis, and secreting neurotrophic factors. Moreover, MSCs can also release exosomes, which may be part of their analgesic effects. Exosomes derived from MSC also have the functional properties of mother cells and have therapeutic potential for treating NPP by promoting cell proliferation, regulating inflammatory responses, reducing cell death, promoting axon regeneration and angiogenesis. Therefore, in this article, we discussed current treatment strategies for NPP and explored the functional role and mechanism of MSCs in the treatment of NPP. We also analyzed the current problems and challenges in the application of MSCs in clinical trials of NPP.